Impact of early enteral nutrition on ventilator associated pneumonia in intubated severe trauma patients: A propensity score-matched study - Wang, Su; Zhao, Xin; Wang, Qian; Wu, Yongran; Xu, Jiaxin; Li, Ruiting; Zhou, Ting; Lv, Zheng; Yang, Jihong; Yang, Le; Zou, Xiaojing (Frontiers in Nutrition, 2023)
Background: Early enteral nutrition is recommended for critically ill patients. However, the impact of early enteral nutrition on intubated severe trauma patients remains unclear. Methods: Severely traumatized adult patients who received invasive mechanical ventilation for more than 48 hours during intensive care unit stay at our institution between 2017 and 2022 were retrospectively included. Early enteral nutrition was defined as enteral nutrition initiation ≤48 hours from intensive care unit admission and late enteral nutrition >48 hours. Propensity score matching analysis was used to compare outcomes between the groups. The primary endpoint was the incidence of ventilator-associated pneumonia. Multivariable logistic regression analysis was performed to identify independent predictors of delayed enteral nutrition. Results: For final analysis, 337 intubated severe trauma patients were available, including 204 (60.5%) in the early enteral nutrition group and 133 (39.5%) in the late enteral nutrition group. After propensity score matching, early enteral nutrition patients had a lower incidence of ventilator-associated pneumonia (12.9% vs. 25.8%, p=0.026) and a shorter length of hospital stay (21 vs. 24 days, p=0.015) compared to late enteral nutrition patients. There was no demonstrable difference in mortality between the two groups. Abdominal trauma, massive blood transfusion, and serum albumin were identified as independent risk factors for delayed enteral nutrition. Conclusions: Early enteral nutrition decreased the ventilator-associated pneumonia rate and reduced the length of hospital stay in invasively ventilated patients with severe trauma. Abdominal injury, massive blood transfusion and low albumin were associated with delayed enteral nutrition.